Early assessment and analysis of high-risk factors of neurodevelopmental impairment in neonates with congenital diaphragmatic hernia - Bai, Boliang; Liu, Wendong; Yu, Ronghui; Zhu, Xueping; Sun, Wenqiang; Jiang, Lang; Wang, Xiaodong; Su, Guanghao (Frontiers in Pediatrics, 2025)
BackgroundThis study aimed to retrospectively analyze clinical data of neonates with congenital diaphragmatic hernia (CDH) to investigate risk factors for neurodevelopmental impairment and their prognosis, and to evaluate the predictive value of combined assessment using amplitude-integrated electroencephalography (aEEG), regional cerebral oxygen saturation (rSO₂), and Neonatal Behavioral Neurological Assessment (NBNA) for early intervention.MethodsA total of 83 neonates with CDH (36 in the neurodevelopmental impairment group and 47 in the control group) were included, all diagnosed by prenatal ultrasound and postnatal imaging, with exclusion of other congenital malformations, hemodynamic instability, and genetic disorders. Clinical data [e.g., lung-to-head ratio (LHR), postoperative pulmonary hypertension, surgical approach], neuromonitoring indices (aEEG, rSO₂), and neurodevelopmental assessments (NBNA, Gesell Developmental Schedules) were collected. Independent risk factors for neurodevelopmental impairment and the area under the ROC curve (AUC) of aEEG, rSO₂, NBNA, and their combined assessment were analyzed.ResultsSevere pulmonary hypoplasia (LHR < 1.5; OR = 6.20, 95% CI: 2.15–17.80, P = 0.005), postoperative persistent pulmonary hypertension (PPHN; OR = 2.80, 95% CI: 1.09–13.60, P = 0.027), and open surgery (vs. minimally invasive repair; OR = 2.80, 95% CI: 0.82–9.58, P = 0.056) were identified as independent risk factors for neurodevelopmental impairment in CDH neonates. aEEG scores and rSO₂ values in the neurodevelopmental impairment group were significantly lower than those in the control group at both 14 and 28 days (P < 0.001). The combined assessment of aEEG, rSO₂, and NBNA showed the highest AUC (0.960), with 83.0% sensitivity and 98% specificity.ConclusionLHR < 1.5, PPHN, and open surgery are independent predictors of neurodevelopmental impairment in CDH neonates. The combined use of aEEG, rSO₂, and NBNA significantly improves the efficiency of early neurodevelopmental impairment identification (AUC = 0.960), outperforming single indicators. Clinicians should prioritize monitoring pulmonary hypoplasia and perinatal complications while adopting multimodal neuromonitoring to optimize early intervention strategies.